Social Entrepreneurship Development Strategy - Febrianto, Abi Sopyan; Khoirunnisa, Rilla; Sudiro, Achmad; Rahayu, Mintarti (Universitas Prasetiya Mulya, 2023)
This study aimed to analyze the strategy of developing social entrepreneurship with the Social Impact Canvas method on Sahawood. This study used a qualitative method with a case study approach. Data collection method was done by using observation and interviews with four informants who were directly involved in the Sahawood business process. The Social Impact Canvas provides an overview of business development strategies contained in the components of anchor purpose; value prepositions; stakeholders; stakeholders relationship; channel; key activities; key resources; key partners; revenue streams; magnitude; costs; differentiation. The findings in this study indicate that the social value of Sahawood creates a strong brand story and becomes a strength in attracting consumers. As a social entrepreneurship, Sahawood was able to become a place for former addicts to change for the better and control the beneficiaries from using drugs again and committing criminal acts. Social Impact Canvas is not only describing business implementation but also highlighting social values and business uniqueness in social entrepreneurship. This study has implications for the development of Sahawood’s future business strategy.